War Work Exhibition leaflet, Leeds, 1941 (Leeds, 1941)
1941 1939-1945 "War Work Exhibition leaflet, Leeds, 1941" [HFR0049], 1941 This leaflet encouraging women to undertake training for war work in engineering was issued by the Ministry of Labour and National Service.